2019
DOI: 10.1002/cbic.201800643
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl‐LacNAc‐PNA⋅DNA Concatamers by Rolling‐Circle Amplification as Multivalent Inhibitors of Influenza A Virus Particles

Abstract: The surfaces of influenza A virus (IAV) particles are packed with hundreds of homo‐trimeric hemagglutinins (HAs). Monovalent sugars have low affinity for HA, but distance‐optimized bivalent sialyl‐LacNAc (SLN) conjugates bind it with 103‐fold enhanced potency. Herein, we describe the oligomerization of distance‐optimized bivalent binders by branched and linear hybridization on long repetitive DNA templates. The most effective complexes fully inhibited IAVs at a DNA template concentration of 10−9 m. Although a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Attachment of the ligand system to PNA provides a further 4.8±1‐fold enhancement of relative potency (IC 50 (Mono‐TriGlc2NTs)=10.5±2.2 μM vs. IC 50 (TriGlc2NTs)=50.5±0.5 μM). The improved affinity upon attachment to DNA scaffolds has also been seen in investigations of other carbohydrate binding proteins [13b, 15g, 32] . As shown in control experiments, unspecific binding of the DNA‐PNA scaffold seems unlikely and we attribute this affinity increase to steric shielding effects [33] .…”
Section: Resultssupporting
confidence: 71%
“…Attachment of the ligand system to PNA provides a further 4.8±1‐fold enhancement of relative potency (IC 50 (Mono‐TriGlc2NTs)=10.5±2.2 μM vs. IC 50 (TriGlc2NTs)=50.5±0.5 μM). The improved affinity upon attachment to DNA scaffolds has also been seen in investigations of other carbohydrate binding proteins [13b, 15g, 32] . As shown in control experiments, unspecific binding of the DNA‐PNA scaffold seems unlikely and we attribute this affinity increase to steric shielding effects [33] .…”
Section: Resultssupporting
confidence: 71%
“…12 and (31)]. Recent biophysical studies with alternative glycan-decorated scaffolds have shown that ∼1000-fold enhancements over monovalent binding to HA can be achieved with only two sialylated ligands, provided the sugars are arranged 50-100Å apart (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Seeking to boost the affinity for IAV particles, we used rolling circle amplification (RCA) to oligomerize the optimized bivalent sialyl-LacNAc assemblies. 36 After hybridization of sugar-containing strands with the long repeating template strand afforded by RCA, the resulting complex could present bivalent LacNAc groups at extremely high effective concentrations. The tandem repeats encoded during RCA provided a binding platform, which we utilized for two different attachment strategies (Fig.…”
Section: Multivalent Interactions With Carbohydrate Receptors On Cellmentioning
confidence: 99%
“…42,45 However, the higher the rigidity of the scaffold, the more closely it must conform to the geometry of the receptor sites to produce a binding enhancement. In the cases of receptor sites with highly complex, curved, or unknown binding geometries, it may be advantageous to reduce the rigidity of the construct, either by introducing nick sites in a dsDNA duplex, 10 leaving regions of unhybridized ssDNA, 36 and/or emphasizing flexible linkers between the oligonucleotide scaffold and the presented ligands. 28 The most commonly employed backbones for multivalent nucleic acid constructs, DNA and PNA, both present unique challenges and opportunities.…”
Section: Overall Trends and Outlookmentioning
confidence: 99%